International note: Prediction of mathematics work ethic and performance from behavioral, normative, and control beliefs among Qatari adolescents - Areepattamannil, S.; Abdelfattah, F.; Mahasneh, R.; Khine, Myint Swe; Welch, A.; Melkonian, M.; Al Nuaimi, S. (2016)
Over half-a-million adolescents take part in each cycle of the Program for International Student Assessment (PISA). Yet often, researchers and policy makers across the globe tend to focus their attention primarily on the academic trajectories of adolescents hailing from highly successful education systems. Hence, a vast majority of the adolescent population who regionally and globally constitute the ‘long tail of underachievement’ often remain unnoticed and underrepresented in the growing literature on adolescents' academic trajectories. The present study, therefore, explored the relations of dispositions toward mathematics, subjective norms in mathematics, and perceived control of success in mathematics to mathematics work ethic as well as mathematics performance; and the mediational role of mathematics work ethic in the association between dispositional, normative, and control beliefs and mathematics performance among adolescents in one of the lowest performing education systems, Qatar. Structural equation modeling (SEM) analyses revealed that Qatari adolescents' dispositional, normative, and control beliefs about mathematics were significantly associated with their mathematics work ethic and mathematics performance, and mathematics work ethic significantly mediated the relationship between dispositional, normative, and control beliefs about mathematics and mathematics performance. However, multi-group SEM analyses indicated that these relationships were not invariant across the gender and the SES groups.